PERILAKU BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 (STUDI TENTANG PERILAKU BELAJAR PESERTA DIDIK KELAS IV SD NEGERI 1 OEBOBO KUPANG TAHUN AJARAN 2020/2021) - Uran, Rosalia Ruth; Kase, Emanuel Bai Samuel; Adinuhgra, Silvester (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2021)
This research was conducted with the aim of finding out how the learning behavior of fourth-grade students at SD Negeri 1 Oebobo Kupang during the Covid-19 pandemic was described and what factors supported and hindered the learning behavior of students at the primary school in question. The research uses qualitative methods with a natural descriptive approach so that it can describe natural conditions and show processes that can explain the occurrence of the phenomenon under study. Data collection in this study was carried out by observation, interviews, and documentation. While the data analysis techniques used in this study consisted of data collection, data reduction, data presentation, and verification or conclusions. The results showed that there was a shift in the learning behavior of students at SD Negeri Oebobo 1 Kupang, especially fourth-grade students. In the online learning process, it turns out that not all students can respond in the form of appropriate learning behavior due to the Covid-19 pandemic. To overcome this problem, there needs to be cooperation between educators and parents to assist, motivate, and direct students in various aspects of every online learning activity that is carried out.